(untitled) (Palimpsesto, 2018)
In the present article the poem No Pasarán! of the writer Octavio Paz will be analyzed from the historical perspective and the support provided by Mexico to the Spanish Republic as a sample of solidarity at the beginning of the Civil War in 1936. The perception of the Mexican writer will be studied since his participation in the Second Congress of Antifascist Writers held in Valencia in 1937 where he gave a speech together with other writers of different nationalities. It will be identified how the experience of the war will influence the creative thought of Paz related to a poetry that describes the support to the republican Spain, putting emphasizing in the idea of what was later called social poetry and how it reflects the feelings of the masses in facts of war or discrimination.